1979
DOI: 10.4039/ent111207-2
|View full text |Cite
|
Sign up to set email alerts
|

Emodin in Buckthorn: A Feeding Deterrent to Phytophagous Insects

Abstract: Emodin, a mixture of anthraquinones, occurs in the Rhamnaceae and functions as a deterrent to foliage-feeding insects. There was little attack on foliage of Rhamnus alnifolia in wild stands compared with associated species of woody plants. Anthraquinones extracted from foliage of R. alnifolia were similar to purchased emodin in thin-layer chromatographic and infra-red spectroscopic analyses. Quantities of emodin in foliage samples were high in May, declining to low levels in August. Leaf powders, leaf extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 7 publications
(1 reference statement)
0
27
0
Order By: Relevance
“…A purgative, anthraquinone is derived from shestrin (Kingsbury 1964;Tampion 1977). The anthraquinone emodin is also prominent in R. cathartica tissues (Trial and Dimond 1979; see also Section 13). Unripe fruits contain saponins (Westbrooks and Preacher 1986).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…A purgative, anthraquinone is derived from shestrin (Kingsbury 1964;Tampion 1977). The anthraquinone emodin is also prominent in R. cathartica tissues (Trial and Dimond 1979; see also Section 13). Unripe fruits contain saponins (Westbrooks and Preacher 1986).…”
Section: Historymentioning
confidence: 99%
“…Insects in North America have not had sufficient time to evolve defences against anthroquinones present in R. cathartica (Trial and Dimond 1979). The green stink bug Acrosternum hilare (Say) has frequently been observed on R. cathartica in Quebec and Ontario (Javahery 1990).…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…EO possesses numerous biological properties, including bactericidal, fungicidal, immunosuppressive, hepatoprotective, and anticancer activities (Srinivas et al, 2007;Martín-Cordero et al, 2012;Qu et al, 2013;Liu et al, 2015;Dong et al, 2016). EO is important in mediating plant-plant (Knight et al, 2007), plant-animal (Trial and Dimond, 1979;Sacerdote and King, 2014), plant-microorganism (Lee et al, 2013), and plant-abiotic environmental interactions (Izhaki, 2002). The principal activity of EO in mediating plant-animal interactions is feeding deterrence (Trial and Dimond, 1979;Georges et al, 2008;Akhtar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Abu-Darwish (2000) isolated and identified 11 compounds from barks of R. This study aimed to test the insecticidal activity of R. dispermus against the PTA, since it has been shown that Rhamnus spp. may contain compounds that act as botanical pesticides, such as emodin (Trial and Dimond, 1979, Singh et al, 1992, Tsahar, 2001Izhaki, 2002) Bark of R. dispermus was collected from AshShoubak, Jordan. Its botanical identification was confirmed by Dr. Talal Abu Rjae, at the University of Jordan, who keeps voucher specimens in his laboratory.…”
mentioning
confidence: 99%
“…This activity could be the result of the aforementioned anthraquinone and flavonoid compounds found in this plant. In larvae of the gypsy moth, Lymantra dispar, the anthraquinone aglycone emodin caused pronounced mortality in 2-3 d (Trial and Dimond, 1979). Malicky et al (1970) indicated that Rhamnus cathartica is attacked by very few insect species due to the presence of emodin and other anthraquinones.…”
mentioning
confidence: 99%